Reaction Mechanisms of Biochar Gasification and Tar Reforming - Liu, Yurong (Curtin University, 2021)
This thesis presents a comprehensive study on the pore structure development in biochar during gasification in H2O, CO2 and H2O/CO2, along with the mechanism of tar reforming using biochar as a catalyst. H2O and CO2 preferably react with different carbon atoms. O-containing functional groups are important in enhancing the catalytic activity of biochar. The findings provide valuable information in better understanding the process of biomass gasification.